Impact of elderly donors for liver transplantation: A single‐center experience. Issue 5 (15th April 2015) - Kamo, Naoko; Kaido, Toshimi; Hammad, Ahmed; Ogawa, Kohei; Fujimoto, Yasuhiro; Uemura, Tadahiro; Mori, Akira; Hatano, Etsuro; Okajima, Hideaki; Uemoto, Shinji
Abstract : Elderly donor grafts for liver transplantation (LT) are recognized to be marginal grafts. The present study investigated the impact of using elderly donors for LT. Between June 1990 and August 2012, 1631 patients received LT at Kyoto University Hospital. Out of 1631 patients, 1597 patients received living donor liver transplantation (LDLT), whereas the other 34 patients underwent deceased donor liver transplantation (DDLT). Seventy‐five grafts that were used came from individuals who were ≥60 years old. We retrospectively analyzed the recipients' survival rates according to donor age. The overall survival rates of the recipients of all LDLT ( P  < 0.001), adult‐to‐adult LDLT ( P  = 0.007), all DDLT ( P  = 0.026), and adult‐to‐adult DDLT ( P  = 0.011) were significantly lower for the elderly donor group versus the younger group and especially for those who were hepatitis C–positive. A multivariate analysis revealed that donor age, ABO incompatibility, and preoperative intensive care unit stay were independent risk factors for poor patient survival in adult‐to‐adult LDLT. However, no significant differences existed between the 2 groups among those who received adult‐to‐adult LDLT in and after April 2006. No significant association was found between donor age and incidence of acute cellular rejection. In conclusion, donor age was closely related to the survival rate for LDLT and DDLT, although the impact of donor age was not shown in the recent cases. Liver Transpl 21:591–598, 2015 . © 2015 AASLD.